Research on Noise Reduction of Spur Gears Based on Viscoelastic Material - Dong Huaiyu; Ming Yuzhou; Zhang Yantao; Jia Xingyun; Qi Fei (Jixie chuandong)
In order to reduce the radiation and conduction noise of the end face of spur gears, on the basis of previous studies, the polymer materials with viscoelastic properties, acrylic ester and polyurethane, are selected and evenly coated on the end face of spur gears. The noise reduction results of different materials and different coating thicknesses are compared. The test results show that the selected polymer materials can reduce the radiated noise of spur gears. Within a certain thickness range, the noise reduction increases with the increase of the coating thickness of the material.